2009
DOI: 10.1155/2009/439107
|View full text |Cite
|
Sign up to set email alerts
|

Is Chronic Inflammation a Possible Cause of Obesity-Related Depression?

Abstract: Adult obesity has been associated with depression, especially in women. Whether depression leads to obesity or obesity causes depression is unclear. Chronic inflammation is observed in obesity and depression. In 63 obese women without additional diseases depression level was assessed with the Beck's questionnaire. After evaluation of depression level study group was divided into groups according to the mood status (A—without depression, B—mild depression, and C—severe depression), and serum concentration of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Our previous study [18] revealed that about 60.0% of obese subjects starting the group weight reduction program had mild or severe depression levels. Similar results were obtained in the present study (52.6%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study [18] revealed that about 60.0% of obese subjects starting the group weight reduction program had mild or severe depression levels. Similar results were obtained in the present study (52.6%).…”
Section: Discussionmentioning
confidence: 97%
“…It has already been proved that occurrence of depression may precede the development of obesity and, quite the reverse, the development of depression may follow development of obesity, moreover, both diseases may develop at the same time [4,5]. Our previous studies [18] revealed that in a population of 217 patients starting the group weight reduction program, the prevalence of depression reached 59%. Numerous recent stud-7 ies have reported that weight loss achieved with a lifestyle modification improved symptoms of depression [19][20][21][22].…”
Section: Introductionmentioning
confidence: 95%
“…The results of a single study revealed that chronic microinflammation related to obesity may be a factor that participates in depression development [45]. However, our study did not confirm this link between obesity and depression [46]. The results of experimental studies have also suggested that gastrointestinal tract hormones, such as ghrelin and peptide YY (PYY), participate in mood disorders development.…”
Section: The Possible Links Between Obesity and Depressionmentioning
confidence: 62%
“…As is known, in depression disorders with regulation of the hypothalamicpituitary adrenal, HPA are observed [47]. Nowadays, participation of proinflammatory cytokines in causing depression, cardiovascular diseases and obesity is emphasized [48], [49]. From animal studies results, it is visible that inflammatory processes are observed also in the exposure to air pollution (PM) [50] and their growth in the hippocampus may be associated with the development of clinical depression [47].…”
Section: Discussionmentioning
confidence: 99%